Fundamentals of quantum mechanics : - Tang, C. L. (Cambridge University Press, 2005)
The basic concepts of quantum mechanics are explained in this book in a concise and accessible manner. Illustrating real-world applications in many diverse fields, it is suitable for students in electrical engineering, materials science and applied physics. It contains many homework problems and worked examples, with solutions available to instructors.